Condicional e 'ir' no Imperfeito + Infinitivo: questões de temporalidade e de modalidade - Cunha, Luís Filipe (Revista da Associação Portuguesa de Linguística, 2017)
In European Portuguese, both the Condicional (approximately corresponding to the English structure would + Infinitive) and the construction ir (‘go’) in the Imperfect + Infinitive express posteriority with respect to a given past interval. In this paper, I show that, in spite of their seemingly similar behaviour, these two forms diverge in a number of significant aspects. In particular, and taking into account the analysis of contexts such as if-clauses and some subordinate complement clauses introduced by factive and intensional verbs, I will argue that, while the Condicional is mainly used to provide modal information, even losing its basic temporal value, the structure ir (‘go’) in the Imperfect + Infinitive always induces a temporal relation of futurity in a past domain, irrespective of the possible modal meanings accompanying it.